Articulating Concepts Matters! Resilient Actions in the Norwegian Governmental Response to the COVID-19 Pandemic; Comment on "Government Actions and Their Relation to Resilience in Healthcare During the COVID-19 Pandemic in New South Wales, Australia and Ontario, Canada" - Sina Furnes Øyri; Siri Wiig (Kerman University of Medical Sciences, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has challenged our healthcare systems and required collaboration from both centralized and decentralized system levels to adapt to the changes and challenges. This commentary offers a look into the Norwegian governmental healthcare system and response within a resilience in healthcare perspective, by analyzing the situated, structural, and systemic resilience. Such a conceptualization of resilience into three scales of organizational activity may assist our efforts to understand and explain governmental actions throughout the pandemic. Research application of resilience in healthcare to explain and discuss government actions during the COVID-19 pandemic, needs to ensure sensitivity to the overall structural, cultural, and human factor aspects of the relevant healthcare system under scrutiny as well as sensitivity to specific context within the various system levels.